(untitled) (Interdisciplinary Studies Journal, 2023)
This study aimed to analyze the possible contributions of a video narrative to the understanding of mathematical concepts in calculating the selling price of a product in an agribusiness. The goal was to characterize this mathematical situation, describing difficulties and limitations arising from the use of mathematical content, which supported the development of the narrative for the promotion of a pedagogical action in the enterprise. Methodologically, the research was framed in a qualitative approach. The creation of the narrative followed the phases of pre-production, production, and post-production, being subsequently validated by expert judges and the target audience. The presented narrative detailed the context of the enterprise with the integration of sound and visual elements to dynamically present mathematical calculations. This material was considered by judges as suitable for the proposal, with the potential to meet users’ needs, pedagogical potential, and an appropriate duration. Members of the agribusiness stated that the material helped in understanding the formation of the selling price of a product. In conclusion, this educational material is a potential resource for learning mathematical content in the formation of the selling price of a product, contributing to the appropriation of this knowledge and consequently strengthening enterprise management.